2023
DOI: 10.1371/journal.pgen.1010410
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference of admixture graphs on Native American and Arctic populations

Abstract: Admixture graphs are mathematical structures that describe the ancestry of populations in terms of divergence and merging (admixing) of ancestral populations as a graph. An admixture graph consists of a graph topology, branch lengths, and admixture proportions. The branch lengths and admixture proportions can be estimated using numerous numerical optimization methods, but inferring the topology involves a combinatorial search for which no polynomial algorithm is known. In this paper, we present a reversible ju… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 28 publications
(42 reference statements)
0
28
1
Order By: Relevance
“…Except for certain cases where Anzick-1 is one source , all other models were rejected, and consequently, we found no evidence of PPE admixture into present-day PNW populations, at least based on our dataset ( Tables S3 and S4 ). We note that it was recently suggested that Saqqaq may not serve as the best proxy for gene flow into the NNA because the PPE source that contributed ancestry to some North American groups may have been more closely related to the Koryak than to the Paleo-Inuit 88 ; however, our results are consistent when the Koryak and Chukchi peoples are used a source.…”
Section: Resultscontrasting
confidence: 49%
“…Except for certain cases where Anzick-1 is one source , all other models were rejected, and consequently, we found no evidence of PPE admixture into present-day PNW populations, at least based on our dataset ( Tables S3 and S4 ). We note that it was recently suggested that Saqqaq may not serve as the best proxy for gene flow into the NNA because the PPE source that contributed ancestry to some North American groups may have been more closely related to the Koryak than to the Paleo-Inuit 88 ; however, our results are consistent when the Koryak and Chukchi peoples are used a source.…”
Section: Resultscontrasting
confidence: 49%
“…To further support our ABC-RF models, we performed an admixture graph estimate using AdmixtureBayes ( Nielsen et al 2023 ). AdmixtureBayes is a Bayesian approach that uses a reversible jump Markov Chain Monte Carlo (MCMC) to find a best-fitting graph that describes the ancestry of the analyzed populations, not requiring a priori information (i.e., a tree topology) on populations splits or the number of admixture events.…”
Section: Methodsmentioning
confidence: 99%
“…To further explore the ancestry of samples, we obtained an admixture graph estimate using AdmixtureBayes (Nielsen et al, 2023).…”
Section: Species Tree and Divergence Times Estimation With Snp Datamentioning
confidence: 99%